(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2020)
The article proposes a pedagogical conception that enhances pro-childhood action in its different contexts of action in Manicaragua. Its construction, in and from the university, fosters transformations in the Cuban educational system in response to vulnerabilities related to family dysfunction, responsible for the occurrence of child abuse. Educational agents, such as teachers who are graduates or in training and outside the educational sector, are trained through the municipal community pedagogical project For a Happy Childhood, the main setting where they get involved cooperatively. The spaces for analysis, reflection, exchange, and decision-making that take place there generate a multiplicity of learning about preventive culture and rights, peaceful environments, well- being and satisfaction as an expression of happiness. These postulates of the conception are consistent with the university-society articulation in its relationship with children, families, communities, the role of teaching and the determination of university content.